Pro-environmental behavior and waste sorting under the theory of planned behavior: a narrative literature review - Oliveira, Henrique Lúcio Hilarino de; Pozo, Osmar Vicente Chevez (Brazilian Journal of Production Engineering, 2025)
The climate emergency and the rising generation of municipal solid waste have placed pro-environmental behavior at the center of global agendas. This article aims to critically review recent literature on the determinants of pro-environmental behavior related to waste sorting, based on the Theory of Planned Behavior (TPB). A narrative literature review was conducted by analyzing 32 empirical articles published between 2020 and 2025, retrieved from Web of Science and Scopus databases. The findings reveal that psychosocial factors (attitudes, subjective norms, perceived control), emotional variables (guilt, pride), and identity aspects (ecological identity) significantly influence waste separation intentions and behavior. Structural factors such as infrastructure, convenience, and institutional support were also found to be key drivers. It is concluded that waste sorting is a multidimensional phenomenon, and effective public policies must integrate environmental education, incentives, accessible technologies, and targeted communication strategies. The study recommends future research to prioritize real behavior, longitudinal designs, and broader geographic contexts.
Keywords: pro-environmental behavior; waste sorting; theory of planned behavior; sustainability; literature review